Evaluation of the power produced by muscles - Havránek, Antonín; Mayer, Martin; Jelen, Karel (Acta Universitatis Carolinae. Kinanthropologica, 2011)
Rheological Maxwell-type model is used to obtain a relation between energy input to aÂ muscle and the work produced by it. The key role in the relation plays the muscle activity 1/Î· which describes how much energy is converted to work in unit volume element at unit time. The activity is the muscle material value describing how much actin-myosin pairs are engaged in a given place to maintain the work production of the whole muscle system. The modelling of the system has been done and it is now possible to calculate the energy input in special muscle system activities by mechanical means.
Keywords: financování organizované; aktomyosin; Statistics as Topic; teoretické modely; statistika jako téma; viskoelasticita; Human Experimentation; svalová kontrakce; tvorba energie; svalová síla; energetický metabolismus; lidé; Rheology; Actomyosin; Energy Metabolism; Muscle Strength; Financing, Organized; biomechanika; experimenty na lidech; reologie; Muscle Contraction; Models, Theoretical; aktino-myozinové dvojice; Biomechanical Phenomena; Humans